A kinematics analysis of the lower limb during running with different sports shoes. (March 2019) - Fu, Lin; Gu, Yaodong; Mei, Qichang; Baker, Julien S; Fernandez, Justin
The study aimed to investigate the differences in lower limb joint angles during running with three different sports shoes: basketball shoes, football shoes, and running shoes. Fifteen male subjects (age: 25 ± 2.2 years, height: 1.79 ± 0.05 m, and mass: 70.8 ± 3.4 kg) were asked to run on a treadmill at their preferred running speed. The Vicon 3D motion analysis system was used to capture the kinematics of the lower extremity during running. A one-way analysis of variance was used to determine whether any statistical significance existed between the three types of shoes (α < 0.05). Significant differences existed in the lower limb joints between the three sports shoes, particularly at the knee joint. Running shoes presented more knee flexion than basketball shoes and football shoes. In the frontal plane, basketball shoes showed less knee abduction than running shoes and football shoes. No significant difference occurred in ankle external rotation between basketball shoes and football shoes, and both of them presented greater range of motion of the ankle and knee than running shoes.